Peran Institusi Lokal Dalam Pembentukan Habitus Siaga dan Pengembangan Mitigasi Bencana di Kawasan Gunung Kelud Kabupaten Kediri - Windiani; I.B. Wirawan; Sutinah (Institut Teknologi Sepuluh Nopember, 2019)
This study aims to explore the role of local institutions in the establishment ofpreparedness habitus and the development of disaster mitigation in MountKelud area of Kediri Regency using the structural-constructivist approach ofPierre Bourdieu. This research is qualitative research in nature so that the datacollection is conducted by participant observation, document tracking, and indepth interview. The results showed that local institutions that play a role inthe formation of disaster prepared habitus and mitigation development in theMount Kelud area are formal institutions e.g. BPBD of Kediri, District andVillage, and informal institutions namely the Jangkar Kelud Community andthe Village Disaster Preparedness Team. The research also found thatcollaborative roles between leaders and local leaders have contributed greatly tothe formation of disaster preparedness habitus for residents of Mount KeludSlopes. In the formation of preparedness habitus and disaster mitigationleaders and local leaders use the knowledge and local wisdom as capital valueto develop the attitude of life